Alat Ukur Peminatan Psikologi (Psikologi Industri dan Organisasi, Psikologi Klinis, Psikologi Perkembangan, Psikologi Pendidikan, dan Psikologi Sosial) Prodi S1 Psikologi Universitas Katolik Widya Mandala Surabaya - Made Dharmawan Rama Adhyatma; Dicky Susilo (Psychopreneur Journal, 2022)
The Psychology Undergraduate Program at the Psychology Faculty - UKWMS has five areas of specialization consisting of Industrial and Organizational, Clinical, Developmental, Educational, and Social Psychology. Students need to adjust their interests to the five areas of specialization so that they can determine their future career orientation according to the field of work that reflects their competence in each area of interest. These specific competencies will be developed through specialization courses in each area of interest. Therefore, students need to know in advance their interests so as not to be careless in taking specialization courses later. On the other hand, measuring tools to identify areas of interest in psychology are still relatively limited, so scientific research is needed to make standardized measuring tools so that later it can help students to determine their area of interest. This interest measurement tool consists of several work situations related to each area of interest in psychology, where the subject will be asked to choose the type of task that he likes the most to the least. The assignments is based on competency standards determined by the Association of Indonesian Psychological Higher Education Providers (AP2TPI). The validity of the measuring instrument is enforced using the criterion validity method. The results of a study of participants who have completed undergraduate education show that 80% of test results are in accordance with the chosen field of interest during college.